PENGAWETAN KAYU SUNGKAI (Peronema canescens jack) MEMAKAI DUA JENIS BAHAN PENGAWET - Sasa Abdurrohim (Jurnal Penelitian Hasil Hutan, 1991)
Air dry sungkai (peronema canescens jack) wood samples, measuring 3 cm x  3 cm (432 samples) were  treated with cold soaking treatment using wolmanit CB and Diffusol  CB  and diffusol CB preseruatibes for 1,2,3,4,5,6,7,8, and 9 daya at the concentrations of 2, 4, 6, and 8 %. The results show  ot the construction sungkai timber  used  under  the root  without  soil contact  can be treated  with both preservatives at the concentration of 6 and 8 %. the soaking duration for each concentration was 9 and 4 days respectively for wolmanit CB preservative, and 7 and 6 days for diffusol  CB. For out door construction without soil contact, the timbers should be treated by 8 % diffusol CB by soaking duration of  9  days.